Alliance of Cinema and Music: the First KINOREX Film Music Festival in the Context of Interaction between Music and Cinema in the Early 21st Century /Cоюз кино и музыки: о первом киномузыкальном фестивале «KINOREX» в контексте проблемы взаимодействия музыки и кино начала XXI века - Ryzhinskiy Aleksander S. / Рыжинский А.С.; Konson Grigoriy R. / Консон Г.Р. (Наука телевидения)
Professor of the Moscow Institute of Physics and Technology Grigoriy R. Konson interviews the rector of the Gnesins Russian Academy of Music, professor Aleksander S. Ryzhinskiy. The interview focuses on how film directors and composers see the role of music in films, with music considered as a twofold phenomenon: film score as such and film scores presented at the First KINOREX Film Music Festival. In the preamble, the interlocutors review current trends in film music. In this vein, they touch upon the psychological concept of the French cinematography, interpretation of the Indian song tradition in endowing films with musicality, Baroque music and modern performance practices applied in the 20th century cinema dramaturgy, the Hollywood way of soundtrack composition as a dominating model in the world cinema, and studies devoted to the works of Alfred Schnittke and Thomas Newman. Based on these examples, the interlocutors come to the conclusion that at the heart of different approaches to the film music composition there must be an organic commonality of views of the film director and the composer. Beyond that, a binding force in the process is the reliance on classical traditions of their artistic interaction: expressing the very essence of a film’s drama through music. The discussion of the First KINOREX Film Music Festival, which was held by the Gnesins Russian Academy of Music in April 2021, naturally fits into this humanistic concept. Analyzing the winning project created by director Nadezhda Shibalova and composer Nikita Yamov, the authors of the interview come to the conclusion that the musical fabric of the screen work reveals the fundamental role of music as an analogue of the film’s ethical idea, which increases the cognitive capacity of the content. Интервью профессора Московского физико-технического института (национального исследовательского университета) Г.Р. Консона с ректором Российской академии музыки имени Гнесиных, профессором А.Р. Рыжинским посвящено обсуждению одной из актуальных тем в современном массовом искусстве — отношению кинорежиссера и композитора к роли музыки в кино, которая рассматривается здесь в контексте двуединого феномена: киномузыки как таковой и Первого молодежного фестиваля в России «KINOREX». В преамбуле обсуждения его участники проводят обзор актуальных трендов киномузыки. В этой связи они затрагивают психологическую концепцию во французском кинематографе, трактовку песенной традиции в омузыкаливании индийского кино, барочную музыку и ее современные перформанс-практики в кинодраматургии ХХ века, голливудский способ создания саундтрека как господствующей модели в мировом кинематографе, а также монографические исследования, посвященные творчеству Альфреда Шнитке и Томаса Ньюмана. Исходя из приведенных примеров, собеседники приходят к убеждению, что в основе разных подходов к созданию киномузыки должна лежать органичная общность взглядов кинорежиссера и композитора. При этом непосредственной скрепой здесь оказывается опора на классические традиции их творческого взаимодействия: выражение музыкой глубокого содержания кинодраматургии. В эту гуманистическую концепцию естественно вписывается обсуждение Первого молодежного фестиваля «KINOREX», проведенного Российской академией музыки имени Гнесиных в апреле 2021 года. И, рассматривая проект победителей этого конкурса-фестиваля — режиссера Надежды Шибаловой и композитора Никиты Ямова, авторы интервью приходят к выводу, что музыкальная ткань экранного произведения выявила принципиальную роль музыки как аналога этической концепции фильма, в результате чего увеличилась когнитивная емкость содержания.